Perbandingan Normatif Tindak Pidana Terorisme: Hukum Pidana Nasional Indonesia dan Fiqh Jinayat - Muhamad Abdul Kholik; Syahrul Anwar; Ahmad Abdul Wasi; Dian May Syifa (Jurnal Sosial Humaniora Sigli, 2026)
This article normatively examines, through a comparative approach, the regulation of terrorism offenses in Indonesian national criminal law and fiqh jinayat, focusing on the concepts and elements of the offense, the structure of sanctions, as well as the underlying principles of punishment and justice. The research employs a normative juridical method with a static comparative approach to Law No. 5 of 2018, Articles 600–602 of the Criminal Code (Law No. 1 of 2023), as well as the constructions of hirabah and al-baghy derived from Qur'an Surah Al-Mā’idah (5):33, Surah An-Nisā’ (4):59, and classical fiqh jinayat literature. The analysis reveals that positive law formulates terrorism as a specific criminal offense characterized by elements of violence and threats, mass terror, widespread victims and damage, as well as ideological and political motives. In contrast, fiqh jinayat classifies it within the categories of hirabah and al-baghy, emphasizing attacks against public security and legitimate authority. Both systems recognize very severe sanctions, including the death penalty; however, positive law tends to be codificative, retributive, and procedural, whereas fiqh jinayat combines strict hudud with flexible ta‘zīr within the framework of maqāṣid al-sharī‘ah. This article recommends a hybrid model that integrates the normative certainty of Law No. 5 of 2018 and the 2023 Criminal Code with the orientation toward the protection of life, property, and public order in fiqh jinayat, while also strengthening deradicalization efforts oriented toward substantive justice and the prevention of recurring harm.Keywords: Terrorism, National Criminal Law, Fiqh Jinayat